Was Archaeopteryx able to fly? Authentic palaeontological practices in a museum programme - Achiam, Marianne; Lindow, Bent Erik Kramer (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2019)
Resumen La educación científica auténtica ha recibido una mayor atención en los últimos años, pero aún no está claro en qué consiste la autenticidad. Aquí, utilizamos conceptos de la Teoría Antropológica de lo Didáctico para acercarnos a la autenticidad. Tomamos como punto de partida un programa de educación de un museo y lo analizamos para determinar en qué constituye su autenticidad. A continuación, utilizamos la Teoría de Situaciones Didácticas para construir un modelo de referencia que constituye una versión optimizada con respecto a la autenticidad del programa. También se discuten brevemente las implicaciones de nuestros resultados. Abstract Authentic science education has received increased attention in recent years, but it remains unclear what constitutes authenticity. Here, we use notions from the Anthropological Theory of the Didactic to approach authenticity. We take a point of departure in an existing education programme in a museum, and analyse it to pinpoint what constitutes its authenticity. We then use the theory of didactical situations as a way to construct a reference model; this reference model constitutes an authenticity-optimised version of the programme. We conclude by briefly discussing the implications of our findings.